The Influence of Price and Quality of Telkomsel Internet Package Products on Reseller Outlet Loyalty in Islamic Economic Perspective - Setyagustina, Kurniasih; Wulansari, Reni; Salahuddin, Salahuddin; Sauri, Sauri; Nurarifah, Rina (Talaa : Journal of Islamic Finance, 2022)
This research is motivated by the case of Telkomsel internet package product competition which is still quite high, where many competitors, both retail players and big players from outside the region enter the Merangin zone area. This study uses quantitative method. Data was collected through a questionnaire which was distributed to 85 respondents at reseller outlets who shopped for Telkomsel products at Telkomsel TAP Merangin. The analysis was carried out by processing data using SPSS 26.0 for windows, then proceeded with validity, reliability, classical assumption tests, multiple linear regression analysis and hypothesis testing using t-test and f-test. The results of the study obtained that the price and quality of Telkomsel internet package products had an effect on resellers’ outlet loyalty, in which there was a simultaneous influence between price and product quality on customers’ loyalty. In the perspective of Islamic economy, price and product quality will have a significant effect on customers’ loyalty, with ethical pricing based on good product quality so that it shows honesty that can increase customers’ trust and they will not be deceived so that their confidence becomes more stable because their rights are protected.